Strategy to Optimize Sharia Financial Management as an Instrument to Improve the Performance of Halal MSMEs in West Sumatra - Erizal Candra Efendi; Ruri Mustika (LPPM Universitas KH. A. Wahab Hasbullah, 2025)
This study examines the optimization of sharia financial management as a strategy to enhance the performance of halal small and medium enterprises in West Sumatra. The background of the research is the limited financial literacy, low utilization of formal sharia financing products, and lack of standardized financial reporting among halal SMEs, which hinder their growth and competitiveness. The study aims to analyze how financial literacy, financing utilization, and transparency in reporting contribute to improving operational efficiency and compliance with sharia principles. The research employs a qualitative descriptive approach, using data collected through interviews, observations, and documentation from halal SMEs in West Sumatra. The findings reveal that financial literacy serves as the foundation for effective management, enabling SME owners to understand and utilize sharia-compliant financing. The utilization of formal sharia financing is still low, and standardized reporting is maintained by only a small portion of SMEs, limiting both internal management and access to external funding. The study also finds that integrating literacy, financing access, and transparent reporting creates a synergistic effect that significantly enhances performance, operational efficiency, and stakeholder trust. The conclusions indicate that optimizing sharia financial management is essential for promoting sustainable growth, compliance with sharia principles, and long-term viability of halal SMEs in West Sumatra. This research provides practical implications for policymakers, financial institutions, and SME support agencies to design targeted interventions that improve literacy, facilitate financing access, and implement transparent reporting systems.